2021
DOI: 10.1007/s12126-021-09422-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Internet Use Promotion Programme on Communication, Internet Use, and the Extent of Social Networks among Low-Income Older Adults

Abstract: We examined whether an internet use promotion intervention influences low-income older adults' communication modes, internet use, and social networks using existing data collected for an intervention. Participants living in public senior housing facilities in the United States (n = 77) completed surveys before and after a 12-week computer and internet training. The six-item Lubben Social Network Scale (LSNS-6) was used to measure the extent of older adults' social networks. The primary mode of communication sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 90 publications
(167 reference statements)
0
7
0
Order By: Relevance
“…Samples in the studies included in our systematic review samples were low-income older adults who ranged between ages fifty and one hundred and six years (one study did not report the age range), with a total of 8623 older adults in all 17 studies. Among these studies, a wide range of low-income financial indicators were observed with annual income of less than USD $5000 on the lower end of the scale or less than 100% poverty level and below USD $35,000 or above 200% poverty level on the higher end of the scale [ 55 , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ]. Studies also reported income-to-needs ratio (amount of income relative to the cost of living) below 1.21 [ 56 ]; and income in the past 30 days of USD $0-$1150 [ 66 ] (four studies did not report the income range or percentage of poverty level) [ [67] , [68] , [69] , [70] ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples in the studies included in our systematic review samples were low-income older adults who ranged between ages fifty and one hundred and six years (one study did not report the age range), with a total of 8623 older adults in all 17 studies. Among these studies, a wide range of low-income financial indicators were observed with annual income of less than USD $5000 on the lower end of the scale or less than 100% poverty level and below USD $35,000 or above 200% poverty level on the higher end of the scale [ 55 , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ]. Studies also reported income-to-needs ratio (amount of income relative to the cost of living) below 1.21 [ 56 ]; and income in the past 30 days of USD $0-$1150 [ 66 ] (four studies did not report the income range or percentage of poverty level) [ [67] , [68] , [69] , [70] ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies also reported income-to-needs ratio (amount of income relative to the cost of living) below 1.21 [ 56 ]; and income in the past 30 days of USD $0-$1150 [ 66 ] (four studies did not report the income range or percentage of poverty level) [ [67] , [68] , [69] , [70] ]. Notably, the sample characteristics were diverse across the studies, such as: homeless-experienced [ 66 ]; homebound due to mobility impairment [ 56 ]; US Medicare beneficiaries [ 60 ]; patients at health centres or urban and rural clinics serving low-income populations [ 55 , 57 , 70 ]; immigrants [ 62 , 67 ]; immigrants living in subsidized independent living residential [ 58 , 59 ]; older adults living with a disability, from subsidized public apartments [ 64 ]; older adults living in public senior housing facilities [ 63 , 69 ]; minorities residing in an affordable housing complex [ 19 ]; marginalized older adults from different racial or ethnic backgrounds [ 68 ]; members of a community centre located in one of the poorest neighbourhoods [ 65 ]; and older adults receiving home-delivered meals from aging-service agency [ 61 ]. In general, the population studied had cognitive impairment, and impairments in executive function [ 66 ]; were being treated for a chronic disease (diabetes, hypertension, dyslipidemia, or cardiovascular disease) [ 55 , 57 ]; had an average of three chronic illnesses, diagnosis of depression and anxiety [ 56 ]; had chronic health conditions, such as arthritis, hypertension, diabetes, chronic pain and asthma [ 19 , 58 , 59 ]; and were mobility impaired, homebound, having moderately severe to severe depressive symptoms [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social networks. Several authors refer to the social advantage of social and community • housing using the social network theory (Deville-Stoetzel et al, 2021), social cohesion (Woodard & Rossouw, 2021), social identity theoretical framework (Winer, Dunlap, St. Pierre, McInnes, & Schutt, 2021), and the social augmentation and social displacement perspective (Kim et al, 2022).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…However, whether improving or worsening social isolation has an impact on medication counts remains unclear. An abbreviated version of the Lubben social network scale 6 (LSNS-6), which measures the extent of social networks in older adults, 5,6 is widely used for its simplicity and ease of administration. 7 Regarding non-English speakers, including Japanese speakers, this abbreviated translated version seems to function better compared with the broader version of the instrument.…”
mentioning
confidence: 99%